2014
DOI: 10.1038/pcan.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

The association between race and treatment regret among men with recurrent prostate cancer

Abstract: BACKGROUND To examine the impact of race on treatment regret among men with recurrent prostate cancer after surgery or radiation. METHODS The prospective Comprehensive, Observational, Multicenter, Prostate Adenocarcinoma (COMPARE) registry was used to study a cohort of 484 men with biochemically recurrent prostate cancer after radical prostatectomy, external beam radiation or brachytherapy. Multivariable logistic regression was used to model the association between race and treatment regret and to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In this study, African Americans had a 1.67 times greater odds of reporting regret than whites and other racial/ethnic groups, after adjustment for age, NCCN risk stratum, comorbidity, educational attainment, and control preference. This finding is consistent with previous studies that observed an almost 2‐fold difference in decisional regret between African Americans and whites who underwent robotic‐assisted laparoscopic prostatectomy or had biochemically recurrent prostate cancer . A third study found no difference in decisional regret across race for prostate cancer patients younger than 65, but greater regret among whites compared with African Americans in patients ≥65 years of age .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, African Americans had a 1.67 times greater odds of reporting regret than whites and other racial/ethnic groups, after adjustment for age, NCCN risk stratum, comorbidity, educational attainment, and control preference. This finding is consistent with previous studies that observed an almost 2‐fold difference in decisional regret between African Americans and whites who underwent robotic‐assisted laparoscopic prostatectomy or had biochemically recurrent prostate cancer . A third study found no difference in decisional regret across race for prostate cancer patients younger than 65, but greater regret among whites compared with African Americans in patients ≥65 years of age .…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with previous studies that observed an almost 2-fold difference in decisional regret between African Americans and whites who underwent robotic-assisted laparoscopic prostatectomy 8 or had biochemically recurrent prostate cancer. 27 A third study found no difference in decisional regret across race for prostate cancer patients younger than 65, but greater regret among whites compared with African Americans in patients 65 years of age. 3 The current study also tested for an interaction between age and race, but no interaction was observed.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, additional outcome measures and patient preferences should be evaluated prior to treatment selection. Toxicity and quality of life have become important endpoints considered by most patients in the process of selecting a treatment modality [25, 26, 27]. Recent reports show that among the primary treatments for prostate cancer (brachytherapy, radical prostatectomy, and external beam radiation therapy – EBRT), brachytherapy has the least effect on over-all quality of life [28].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous difficult decisions that patients with advanced prostate cancer must make, including treatment options, cost of care, and family involvement; however, over time patients with advanced cancer often regret some past decisions 68 . Many factors may increase the likelihood that patients will not have complete information at the time it is needed in order to optimize decision making, for example time constraints, forgetting to ask questions, and provider-patient miscommunication 912 .…”
Section: Introductionmentioning
confidence: 99%